THE DETERMINANTS OF COMPANY’S FINANCIAL DISTRESS - Jonnardi, Jonnardi; Bangun, Nurainun; Natsir, Khairina (Graduate Program of Universitas Tarumanagara, 2023)
An economic recession like the current one due to the global pandemic is causing financial difficulties for many companies. Nowadays it is important for companies to be aware of and observe their financial condition. Financial distress is a bad condition impression of a company when the company is no longer able to generate sufficient income or profit, so that its financial obligations cannot be paid. Financial distress is an early symptom of corporate bankruptcy. This study aims to obtain empirical evidence about the effect of profitability, size of the board of directors, and institutional ownership on financial distress. The companies used in this study were 63 companies taken from the various industrial sectors and the basic & chemical industrial sector listed on the Indonesia Stock Exchange in 2017-2019. Purposive sampling was used in this study to determine the sample. Multiple regression panel data and the EViews 11 application are used as data analysis tools. Some of the tests carried out were multicollinearity test, Chow test, Hausman test, t test and coefficient of determination test. The results showed that profitability, board of director’s size and institutional ownership have affecting significantly on financial distress.